Content of Religious Moderation in Catholic Religious Education at Two State Junior High Schools in Landak West Kalimantan Regency - Kristianus Kristianus (IJECA (International Journal of Education and Curriculum Application), 2021)
The background of this research is the Indonesian government's policy related to religious moderation. The aim is to see if Catholic religion teachers can reconstruct and apply the content of religious moderation in the Catholic religious education textbooks for grade 7 State Junior High Schools in Landak Regency. The conclusion obtained from this is that Catholic religious teachers have carried out religious moderation, namely by integrating content and the process of building multicultural insightful knowledge construction. The way he does this is by modifying teaching materials and teaching methods that reach all students, providing examples of diversity, primordialism, stereotypes, mutual respect and respect for religion, culture, and gender-based on the material contained in the Catholic Religious Education curriculum and good manners This is evidenced by students' responses to the integration of content and the process of building knowledge construction with multicultural insight by 65% of students in the "Good" category. In this way, his religious moderation becomes clearer. While reducing prejudice is done by giving explanations and examples to students with an emphasis on mutual respect and respect for each other, honesty, responsibility, self-acceptance of past bitter experiences. This is evidenced by the students' responses to the application of equality pedagogy and reducing prejudice through learning Catholicism by 69% in the "Good" category